Humeral head resurfacing in central bone defects: In vitro stability of different implants with increasing defect size - Kasten, Philip; Neubrech, Christine; Raiss, Patric; Nadorf, Jan; Rickert, Markus; Jakubowitz, Eike (Journal of orthopaedic research, 2012)
We examined the rotary motions of two distinct cementless surface replacement arthroplasties of the shoulder that were implanted on humeri with central spherical bone defects of 8%, 17%, and 37% of the head volume (n = 5 each). Rotary motions were measured under a cyclic torque application and translated into relative micromotions. Implant A with a perforated central crown had micromotions < 150 µm in all bony defects and during all simulated shoulder activities. Implant B with a central tapered tri-fin pin had no micromotions > 150 µm in defects of 0% and 8% during a strenuous activity like lifting 10 kg, but did exhibit micromotion > 150 µm in 40% of the experiments in defects of 17% and 37%, which could impair bony ingrowth. Implant B displayed a significant increase in micromotions for defects of 8% and 17% (p < 0.05). Our results suggest that implant A could be used without risk in spherical head defects up to 37% of volume, even in strenuous shoulder activities immediately after its implantation. Implant B, however, is recommended in spherical defects starting from 8% and only during light shoulder activities until bony integration of the implant has occurred. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 30:1285-1289, 2012